Uncombable hair syndrome. A new evidence for autosomal dominant inheritance. - Selvaag, E.; Thune, P. (European Journal of Pediatric Dermatology, 2018)
We present a three-year-old boy with uncombable hair. The past few months his mother had noted hair loss when she tried to brush his hair. In addition the boy suffered from atopic eczema since early childhood. The father of the boy and his half-sister, the father’s daughter, presented the same ultrastructural changes typical for this syndrome, i.e. longitudinal grooves in the hairs. These findings are in accordance with earlier presentations which suggest an autosomal dominane mode of inheritance in the uncombable hair syndrome.